VARIASI DERMATOGLIFI MAHASISWA DARI PERKAWINAN BERBEDA SUKU DI FKIP UNIVERSITAS LABUHANBATU - Ika Chastanti (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
Dermatoglyphics is derived, and each individual has a different fingerprint pattern even if they are born twins. Fingerprint patterns generally divided into three models, namely Arch, Loop, and Whorl. Fingerprints can widely used as a means of identifying a person in terms of biological decline and differences between ethnic groups. The purpose of this study was to determine variations in dermatoglyphics in students at FKIP Labuhanbatu University from different ethnic marriages. The sampling technique in this study is Purposive Sampling. The method of taking fingerprints is done by sticking student fingerprints on a piece of paper using a blue stamp bearing. The type of fingerprint only observes the results of fingerprint collection. The results showed that variations in the types of fingerprint patterns were found in students with Malay-Javanese, Malay-Batak, Javanese-Batak parental by having Arch, Loop, and Whorl. The most commonly found fingerprint pattern is the Loop type, with a percentage of 71.7% (Javanese - Batak), 61.8% (Batak - Minang), and 60% (Aceh - Batak).